VD_FINDINFO Arrêt-sur-appel / 2010 / 1 vom 19. November 2010 - VD Tribunal cantonal (2010)
MESURE PROVISIONNELLE, PRINCIPE DE LA CONFIANCEINTERPRÉTATION DU CONTRAT | 18 al. 1 CO, 418r CO, 101 CPC, 107 CPC